(untitled) (Journal of Economic Research & Business Administration, 2023)
In the article, the authors substantiate the relevance of the Kazakh model of health insurance, built on a combination of compulsory health insurance (CHI) and the system of budget financing. The purpose of the study is to identify the existing problems that impede the effective development of compulsory medical insurance to improve the program of state guarantees and mechanisms (financial and organizational) for the functioning of participants in the compulsory medical insurance system, highlighting the special role of a citizen as the main stakeholder in receiving free medical care of decent quality. To study this problem, an empirical comparative method was chosen, which made it possible to analyze foreign models of healthcare financing, their advantages and disadvantages, as well as a comparison with Kazakhstan. To analyze the prospects for the formation and functioning of the compulsory health insurance system in Kazakhstan, such classical methods as synthesis and analysis were used. The results obtained made it possible to consider promising areas for financing the healthcare industry from the point of view of solving, first of all, financial and legislative regulation of the CHI system. The article schematically shows the general mechanism for the implementation of CHI. An analysis of the current state of compulsory medical insurance in the Republic of Kazakhstan and its effectiveness through the evaluation of a number of indicators is presented. 3 types of CHI problems in the Republic of Kazakhstan are identified and listed: general, financial and organizational, which made it possible to develop recommendations for improving the efficiency of the CHI system in the Republic of Kazakhstan. Key words: compulsory health insurance, compulsory social health insurance, financing model, healthcare.